Epidemiological data of national Kawasaki disease registry in Iran, 2007–2019 - Shahbaznejad, Leila; Hosseininasab, Ali; Mahboobi, Leila; Mohammadi, Hamid; Esmaeili, Hassan; Farrokhi Far, Seyed Majid; Alipour, Mohammad Reza; Sedighi, Iraj; Mansour Ghanaei, Roxana; Sobouti, Behnam; Taremiha, Alireza; Malek, Abdol Reza; et al. (Frontiers in Pediatrics, 2023)
Introduction. Kawasaki disease(KD) is a vasculitis of childhood that tends to influence the coronary arteries. There is no national data about the prevalence of KD in Iran. This study aimed to perform a national registry in Iran for 13 years. Methods. In this retrospective study, the data for KD extracted from medical records of <19 year-old patients admitted to tertiary hospitals in Iran between 2007-2019 were recorded in the national KD registry system. Age, admission date, gender, location, and presence of KD criteria, laboratory and echocardiography findings, and treatment modalities were evaluated. Complete KD was considered if ≥4 clinical criteria of the KD existed and otherwise, incomplete KD was considered. Results. Data from 1682 KD patients including 999(59.39%) boys and 683(40.61%) girls and male/female ratio of 1.46 were evaluated. The mean age was 3.08±2.49 years and 1465(87%) were living in urban regions. The yearly incidence of the disease was between 2.62 to 3.03 from 2015 to 2019. The highest age-specific incidence was observed in children <1-year-old. Incomplete and resistant KD included 1321(78.54%) and 9(0.54%) patients, respectively. Abnormal echocardiography was detected in 619(36.80%) patients. Leukocytosis, with dominancy of neutrophils, anemia, thrombocytosis and increased ESR and CRP were the most noticeable laboratory findings. No death due to KD disease was reported. Conclusion. Based on this study, most of the KD cases are presented with atypical presentation in Iran. So, increasing awareness of primary healthcare workers by educating and updating their data is very important in timely diagnosis and management of the disease.